2019
DOI: 10.1093/cdn/nzz101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Epigallocatechin-3-Gallate for Prevention of Chronic Kidney Disease and Renal Fibrosis: Preclinical Evidence

Abstract: Chronic kidney disease (CKD) is a common public health problem worldwide characterized by gradual decline of renal function over months/years accompanied by renal fibrosis and failure in tissue wound healing after sustained injury. Patients with CKD frequently present with profound signs/symptoms that require medical treatment, mostly culminating in hemodialysis and renal transplantation. To prevent CKD more efficiently, there is an urgent need for better understanding of the pathogenic mechanisms and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 102 publications
0
27
0
Order By: Relevance
“…In order to prevent the overactivation of the TLRs, several strategies have been developed: (a) To reduce the IL-1β/IL-1R1 signaling pathway several authors have used anakinra (an antagonist of the IL-1R1 receptor) or anti-IL-1β monoclonal antibodies (reviewed in [10,24]); VX765 (an inhibitor of caspase 1, although its use has been dismissed because of its hepatic toxicity [16]); minocycline [25], or natural products such as epigallocatechin gallate (EGCG) or punicalagin ( [26,27], reviewed in [28]), although caution should be taken when the possible utility of these compounds is considered, as, at least in the case of EGCG, it is regarded a pan-assay interfering compound [29]. In all these cases, the administration of any of these compounds decreases the appearance of seizures, at least in animal models of epilepsy (reviewed in [10,24]) ( Table 1) (Figure 1, names in red).…”
Section: Myd88-independent Pathwaymentioning
confidence: 99%
“…In order to prevent the overactivation of the TLRs, several strategies have been developed: (a) To reduce the IL-1β/IL-1R1 signaling pathway several authors have used anakinra (an antagonist of the IL-1R1 receptor) or anti-IL-1β monoclonal antibodies (reviewed in [10,24]); VX765 (an inhibitor of caspase 1, although its use has been dismissed because of its hepatic toxicity [16]); minocycline [25], or natural products such as epigallocatechin gallate (EGCG) or punicalagin ( [26,27], reviewed in [28]), although caution should be taken when the possible utility of these compounds is considered, as, at least in the case of EGCG, it is regarded a pan-assay interfering compound [29]. In all these cases, the administration of any of these compounds decreases the appearance of seizures, at least in animal models of epilepsy (reviewed in [10,24]) ( Table 1) (Figure 1, names in red).…”
Section: Myd88-independent Pathwaymentioning
confidence: 99%
“…This research has shown that EGCG treatment can improve renal function can be and histopathology in kidney function-impaired mice (116). The treatment also regenerated Nrf2 and its downstream products, including a catalytic subset of glutamate-cysteine ligase, a subunit modification of glutamate-cysteine ligase, and glutathione peroxidase (GPx) (116). Funamoto et al also reported that EGCG may have a renoprotective effect after cardiopulmonary bypass in diabetic rats (117).…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 94%
“…In a mouse model of crescentic glomerulonephritis, the therapeutic potential of EGCG was also demonstrated. This research has shown that EGCG treatment can improve renal function can be and histopathology in kidney function-impaired mice (116). The treatment also regenerated Nrf2 and its downstream products, including a catalytic subset of glutamate-cysteine ligase, a subunit modification of glutamate-cysteine ligase, and glutathione peroxidase (GPx) (116).…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 99%
“…In these conditions of severe injury, together with an overload of reactive oxygen species (ROS), these cytochromes spill from the mitochondrion’s inner membrane and may overwhelm the capacity of HO-1 to convert the cytochromes to more inert compounds [ 18 ]. Moreover, ROS may disrupt the intracellular metabolic structure and also the proximal tubular cell super structure of the kidney which is, together with the heart, a mitochondria rich organ relative to tissue mass [ 23 ], and this could have a role in the progression of kidney disease [ 24 , 25 ]. Adenosine triphosphate depletion and loss of the mitochondrial membrane potential required for oxidative phosphorylation, renders the process irreversible with cellular necrosis [ 19 ].…”
Section: Ischemia-reperfusion Injury (Iri)mentioning
confidence: 99%
“…The epigallocatechin-3-gallate (EGCG), an abundant phytochemical polyphenol derived from Camellia sinensis, may promote the preservation of mitochondrial function through the activation of nuclear factor erythroid 2-related factor 2 (Nrf2)/HO-1 signaling, and this results in upregulation of antioxidant or detoxifying enzymes [ 23 ], finally preserving the renal function [ 26 ].…”
Section: Ischemia-reperfusion Injury (Iri)mentioning
confidence: 99%